Corregir lo ambiguo: discursos sobre la ambigüedad en los científicos del género y en los grupos conservadores - Sequeira Rovira, Paula (2023)
This article aims to highlight the importance of looking at ambiguity as a concept that has been used to produce the gender category, to restore those who move away from dichotomous standards, or to demand the elimination of the gender perspective. The paper analyzes the ideas about ambiguity that early scientists theorized about gender and contrasts them with those used by conservative Christian groups to refer to gender ideology. The reviewed documents are based on critical discourse analysis (CDA). The article will try to demonstrate how medical and conservative discourse has proposed ambiguity as the reason for normalizing people’s bodies and subjectivities. Although they appear to be two separate schools of thought, both have many similarities because they are based on the belief that it is necessary to correct ambiguity to fit into dichotomous patterns of normality. The figure of the zombie appears again in the conclusions as a metaphor that can be used to link the two thoughts concerning their ideas of normality and nature.